2015
DOI: 10.1186/s12906-015-0680-x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of berberine hydrochloride and palmatine hydrochloride against Microsporum canis -induced dermatitis in rabbits and underlying mechanism

Abstract: BackgroundPhellodendron amurense, exhibits antifungal activity mainly by bioactive components including berberine hydrochloride and palmatine hydrochloride. This study was conducted to evaluate the antifungal effects of berberine hydrochloride, palmatine hydrochloride, and a mixture of both substances against Microsporum canis in vivo and in vitro.MethodsThe minimal inhibitory concentrations (MICs) of monomers and clotrimazole were determined using 1.5 % tryptic soy agar. The effects of these drugs on Microspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Berberine has shown antifungal activity against Candida albicans (MIC = 34.52 µg/mL) (Zhao et al ., ), Microsporum canis (Xiao et al ., ) and B . cinerea (Parvu et al , ).…”
Section: Antimicrobial Effectsmentioning
confidence: 97%
“…Berberine has shown antifungal activity against Candida albicans (MIC = 34.52 µg/mL) (Zhao et al ., ), Microsporum canis (Xiao et al ., ) and B . cinerea (Parvu et al , ).…”
Section: Antimicrobial Effectsmentioning
confidence: 97%
“…PAL exhibits diverse biochemical and pharmacological functions on jaundice, dysentery, hypertension, inflammation, bacterial, virus and fungal infections with less host toxicity (Vollekova et al, 2003; Ishikawa et al, 2016; Wu et al, 2016). Xiao et al (2015) reported that PAL in combination with berberine (BER) presented remarkably strong antifungal activities to treat Microsporum canis -induced dermatitis in rabbits. Besides, increasing evidence also favored the anti- Candida effects of PAL, inferring that PAL might deserve for further reversion study of resistance especially to azoles (such as FLC and ITR) and underlying mechanism, for example, related with efflux pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in vitro study demonstrated its efficacy against M. canis , with a MIC of 2.92 μM. The mechanism underlying the antimycotic effect of the alkaloid was the disruption of the fungal cell walls, cell membranes, and organelle damage (Xiao, Ji, Wei, Liu, & Bao, ). In another publication, this compound showed an antifungal activity against azole resistant Candida strains, with MIC values in the range of 93.46–373.82 μM.…”
Section: Pharmacology Of Pltmentioning
confidence: 99%